Light Emission of Self‐Trapped Excitons in Inorganic Metal Halides for Optoelectronic Applications. Issue 52 (11th June 2022) - Guo, Qingxun; Zhao, Xue; Song, Boxiang; Luo, Jiajun; Tang, Jiang
Abstract: Self‐trapped excitons (STEs) have recently attracted tremendous interest due to their broadband emission, high photoluminescence quantum yield, and self‐absorption‐free properties, which enable a large range of optoelectronic applications such as lighting, displays, radiation detection, and special sensors. Unlike free excitons, the formation of STEs requires strong coupling between excited state excitons and the soft lattice in low electronic dimensional materials. The chemical and structural diversity of metal halides provides an ideal platform for developing efficient STE emission materials. Herein, an overview of recent progress on STE emission materials for optoelectronic applications is presented. The relationships between the fundamental emission mechanisms, chemical compositions, and device performances are systematically reviewed. On this basis, currently existing challenges and possible development opportunities in this field are presented. Abstract : Their fundamental emission mechanism endows self‐trapped‐exciton (STE)‐emission metal halides with unique optoelectronic properties and broad applications. Recent progress on STE emission materials for optoelectronic applications, and the mechanisms–compositions–application relationships are systematically discussed. Current existing challenges and possible development opportunities are proposed for their further development.